Cine y televisión irlandeses – 2019 - Roddy Flynn; Tony Tracy (Estudios Irlandeses, 2020)
Sometimes, even an annual review feels like it might be too frequent, especially if its subject is an industry wherein the activity often fails to resolve itself within neat 12 months intervals. The policies put in place to incentivise production and the broader development of the screen sector in Ireland operate across five year horizons. Even for individual productions, the gap between a greenlight for production and the actual appearance of the text via whatever primary platform may span several years. (This is particularly true of labour intensive sectors like animation. Cartoon Saloon’s Nora Toomey is currently working on a feature version of Ruth Stiles Gannett’s classic 1948 children’s book My Father’s Dragon which was commissioned in 2018 but which will not see the light of day until 2021).